2016
DOI: 10.1177/1362361316665792
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Early Start Denver Model in an Italian community

Abstract: Identifying effective, community-based specialized interventions for young children with autism spectrum disorder is an international clinical and research priority. We evaluated the effectiveness of the Early Start Denver Model intervention in a group of young children with autism spectrum disorder living in an Italian community compared to a group of Italian children who received treatment as usual. A total of 22 young children diagnosed with autism spectrum disorder received the Early Start Denver Model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 22 publications
10
61
0
4
Order By: Relevance
“…This model had an area under the receiver operating characteristic (ROC) curve (AUC) of 90.7% and a cut-off could be chosen with 100% sensitivity and 72% specificity ( Figure 2). At 18 months, the bivariate logistic regression analysis allowed us to identify 17 Q-CHAT items that were significantly associated to positivity to ASD or BAP (1,2,3,4,5,6,7,8,9,10,14,15,16,17,19, 20, 23 and 25; p < 0.05). Again, starting from these items, we carried out a multivariate logistic regression adopting a stepdown procedure and obtained a model with 4 significantly associated items: item 10 ("Does your child follow where you're looking?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model had an area under the receiver operating characteristic (ROC) curve (AUC) of 90.7% and a cut-off could be chosen with 100% sensitivity and 72% specificity ( Figure 2). At 18 months, the bivariate logistic regression analysis allowed us to identify 17 Q-CHAT items that were significantly associated to positivity to ASD or BAP (1,2,3,4,5,6,7,8,9,10,14,15,16,17,19, 20, 23 and 25; p < 0.05). Again, starting from these items, we carried out a multivariate logistic regression adopting a stepdown procedure and obtained a model with 4 significantly associated items: item 10 ("Does your child follow where you're looking?…”
Section: Resultsmentioning
confidence: 99%
“…Clear evidence exists that early detection and early intervention can lead to a better prognosis [2][3][4]. According to the latest revision of the American Academy of Pediatrics (AAP) guidelines about promoting optimal development in infants and young children, the early identification of developmental disorders should be conducted through developmental surveillance and periodic screening at each pediatric health visit [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both behavioral and developmental strategies were utilized together in three of these studies as Early Start Denver Model (ESDM) to improve social, cognitive, and behavioral skills for preschool children with ASD (Colombi et al, 2018;Vivanti et al, 2014), both studies showed that both groups demonstrated improvements in the targeted skills but ESDM groups achieved higher gains compared to control groups. Further, Joint Attention Symbolic Play Engagement and Regulation (JASPER) model were used to improve the social communication skills, and the study demonstrated significant improvement over the waitlist group in domains of gestures and language joint attention and joint engagement (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There were limitations in the analyzed studies: some studies limited to one category of ASD or use small sample size (Barber et al, 2016;Radley et al, 2015Radley et al, , 2017Ventola et al, 2014;Vivanti et al, 2014;Waugh & Peskin, 2015;Chang et al, 2016). Besides, some studies did not have a control group (Barber et al, 2016;Radley et al, 2015Radley et al, , 2017Reis et al, 2018;Ventola et al, 2014;Fava et al, 2011;Colombi et al, 2018), or not randomly assigned (Zachor & Ben Itzchak, 2010;Waugh & Peskin, 2015). Furthermore, participants in some study were receiving other intervention or services besides the implementation of the intervention program (Reis et al, 2018), or the external factor e.g.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Autism is characterized by developmental difficulties in communication, social interaction and behavioral flexibility, alongside highly repetitive stereotypical behaviors and/or restricted interests [3]. Identifying effective, community-based specialized interventions for young children with autism spectrum disorder is an international clinical and research priority [4]. There exists considerable phenotypic variation of ASD involving the pace of language development, the presence of epilepsy and the range of cognitive ability.…”
Section: Introductionmentioning
confidence: 99%